Crossing borders, addressing diversity. (31st May 2016) - Canagarajah, Suresh
Abstract : This paper presents a story of applied linguistics from my personal vantage point as a multilingual scholar whose career began outside the centers of research and scholarship. The article explains the assumptions and practices characterizing the foundation of the discipline in modernist discourses, and delineates the changes resulting from globalization towards postmodern discourses that question positivistic inquiry and homogeneity. As applied linguistics evolves to address diversity as the norm, the article identifies the different schools that have gradually moved the field in that direction – e.g., variationist applied linguistics (VAL), critical applied linguistics (CAL), postmodern hybridity, and translingual practice. Through these movements, the field has also evolved fromlinguistics applied (LA) to a more theoretically plural and, currently, to a more agentive relationship with other disciplines. Rather than simply borrowing from other disciplines, applied linguists have begun to make their own contributions to those disciplines on language-related issues.